2018
DOI: 10.17675/2305-6894-2018-7-2-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of grape pomace extract and its active components as effective vapour phase corrosion inhibitor of mild steel

Abstract: The inhibition efficiency of grape pomace extract (GPE) and its main constituents (2-phenylacetaldehyde, hexanal) as a green volatile corrosion inhibitor for the temporary protection of mild steel was investigated. Weight loss measurements and potentiodynamic polarization techniques were all used for this assessment. The major constituents of GPE were identified by GC-MS analysis. Grape pomace extract inhibited mild steel corrosion under conditions of periodic condensation of moisture with a protection efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…The relatively poor protection afforded by apricot pomace extract on steel at the initial immersion compared to the results obtained at longer exposure suggests that the formation of a highly protective and stable inhibitor layer on steel surface might need more time than 1-30 h to evolve completely. Similar results were obtained for steel corrosion inhibition by grape and rape pomace extracts in conditions of periodic condensation of moisture [35][36][37][38][39][40][41]. When the immersion time was prolonged beyond 210 h, a decrease of the stability of the protective layer was observed as result of desorption of APE molecules and/or diffusion process through the interface protective layer/electrolyte (see Figure 3).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The relatively poor protection afforded by apricot pomace extract on steel at the initial immersion compared to the results obtained at longer exposure suggests that the formation of a highly protective and stable inhibitor layer on steel surface might need more time than 1-30 h to evolve completely. Similar results were obtained for steel corrosion inhibition by grape and rape pomace extracts in conditions of periodic condensation of moisture [35][36][37][38][39][40][41]. When the immersion time was prolonged beyond 210 h, a decrease of the stability of the protective layer was observed as result of desorption of APE molecules and/or diffusion process through the interface protective layer/electrolyte (see Figure 3).…”
Section: Resultssupporting
confidence: 81%
“…In Figure 6 (2), the FTIR spectrum of steel exposed in 0.5 M NaCl solution containing extract of apricot cake shows the stretching frequencies shifting to 1786 cm −1 , 1515 cm −1 , and 1711 cm −1 for C-H, C=C, and C=O vibrations, respectively. These band shifts confirm that the green inhibitor chemically and/or physically interacts with the metal surface [38,39]. The intense band at 1752 cm -1 appeared is characteristic of ν (C=C) groups maybe corresponding to new groups of compounds (dimeric and trimeric polymer adducts) [10,34].…”
Section: Resultssupporting
confidence: 57%
“…The authors of [11] obtained an extract from rape (Brassicaceae) waste and studied its componential composition. The authors of [12] showed that a promising form of plant material for synthesizing organic compounds is the use of waste from grape processing. The authors determined the phyto-chemical composition of the grape skin extract and made the quantum-chemical calculations of the main components.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The authors of [13] and [14] report on the use of vanillin extract and phenolic compounds, respectively, in corrosion-resistant coatings. However, it should be noted that studies [11][12][13][14] report on the use of isopropyl alcohol in the extraction, which is not common in the synthesis of nanomaterials.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Attempts to find eco-friendly, inexpensive and efficient corrosion inhibitors are still intensively underway. A potential candidate as a corrosion inhibitor is natural product compounds [2][3][4][5][6]. Natural product compounds generally utilize their heteroatom groups (O, N, and P) and their π electron to interact with metal for inhibiting corrosion processes [7].…”
Section: Introductionmentioning
confidence: 99%